Dengue Convalescent Rash in Adult Indonesian Patients - Erni J. Nelwan; Herdiman T Pohan (Acta Medica Indonesiana)
Dengue hemorrhagic fever is still a serious problem in Indonesia. Since the first cases reported in 1968, incidence rate has increased and around 37.3/100.000 populations was infected with the Dengue virus in 2012 with case fatality rate of 0.9%.